Curriculum design for a diploma course for teachers from Cunori University: Focus on in-situ monitoring in agriculture and defining the research portfolio in collaboration with CGIAR / Diseño del diplomado “Herramientas digitales para la investigación, colecta, monitoreo y anailsis de datos de sistemas agropecuarios y ambientales” y portafolio de Iivestigaciones - Martínez, Jesús David; Jimenez, Daniel Ricardo; Ramos, Gresia Dalal; Bonilla, Melissa; Estrada Vargas, Oscar; Muñoz, Luis Armando; Van Loon, Jelle Filip (2023)
This document outlines the collaborative agreements between CUNORI University and CGIAR, specifically focusing on the "Digital Innovation" and "AgriLAc Resiliente" initiatives. The partnership aims to enhance digital agriculture and monitoring systems in Guatemala's Corredor Seco region, building resilience against local challenges. Key aspects of this collaboration include: (i) Diploma Course Development: We detail the modules, dynamics, and structure of a diploma course designed for teachers. This course equips educators with the necessary tools and methods in digital agriculture, aligning with CGIAR's initial intention to first train teachers, who will then impart knowledge to their students.(ii) Research Portfolio Co-Development: In response to regional needs, a research portfolio was co-developed with CUNORI University. This portfolio addresses specific agricultural challenges in the Corredor Seco and aims to foster sustainable practices through innovative research